Adult Congenital Heart Disease (ACHD): A Crack of Our Medical System - Fatema Begum, Nurun Nahar; Kamal Pasha, AKM Mustafa (Journal of Armed Forces Medical College, Bangladesh, 2022)
Abstract not available JAFMC Bangladesh. Vol 17, No 1 (June) 2021: 1-2